Protective effects of methanolic extract of Vicia cracca against hypoxia-induced lethality in mice - razieh shahnazi; mohamamd ali ebrahimzadeh (Mazandaran University of Medical Sciences, 2017)
Vicia genus has 45 species in Iran. Many protective and biological activities have been reported from these species.  In spite of many works, nothing is known about protective effect of V. cracca against hypoxia conditions. In this study, protective effects of V. cracca extract against hypoxia-induced lethality in mice were evaluated by three experimental models of hypoxia, asphyctic, haemic and circulatory. Statistically significant protective activities were observed in some doses of extract in three models. Antihypoxic activity was especially pronounced in asphyctic model. Extract at 200 mg/kg prolonged survival time (27.37 ± 4.0 min) but was not comparable with that of phenytoin (39.80 ± 1.92). At 100 mg/kg it also prolonged survival time (24.76 ± 3.7 min) which was so higher than control group. In haemic model, V. cracca extract signiﬁcantly and dose dependently prolonged survival time as compared to control group. At 200 mg/kg, extract was being capable of keeping the mice alive for 15.38 ± 1.93 min. It was also effective in circulatory model. V. cracca extract at 200 mg/kg prolonged survival time (16.84 ± 1.47 min) that was statistically significant as compared to control group (13.14 ± 0.51 min). V. cracca extract showed a very good protective effect against the hypoxia in some models. Specifically, they produced significant and dose-dependent effect on the model of asphytic and haemic hypoxia. The presence of polyphenols in this plant may be a proposal mechanism for reported antihypoxic activities of this plant.